Hypopharyngeal carcinoma with laryngeal invasion: case report (Research, Society and Development, 2022)
Cancer is a disease that greatly affects the world population. The neoplastic lesions that affect the head and neck regions have a high incidence and aggressiveness, the diagnosis of such lesions often ends up being made at an advanced stage, which contributes to the limited prognosis and survival of the patient. Head and neck cancer is the fifth most common cancer in the world, being one of the main causes of morbidity and mortality in Brazil. Thus, the aim of the study was to describe the clinical and epidemiological profile of a patient with squamous cell carcinoma of the hypopharynx with laryngeal invasion. The case is a 78-year-old man diagnosed with piriform sinus cancer, the most common type of hypopharyngeal cancer. Therefore, primary radiotherapy was the therapy of choice, given the high probability of cure or improvement in cancer symptoms and with fewer risk factors. The advanced stage of the cancer and the late diagnosis of the patient made treatment difficult, being, therefore, a worrying factor, considering the high mortality rate.